Entrepreneurship Development in Management of Intra School Student Organizations in SMA/ SMK Level in the East Indonesian Province (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Understanding of entrepreneurship and organizational management, especially at the OSIS and MPK levels, is still deficient. With a lack of understanding related to entrepreneurship and organizational management at the school level, lecturers at the Faculty of Social and Political Sciences (FISIP) Unjani organize Education and Training for OSIS at the SMA/SMK in the Eastern Province of Indonesia. The method used in this community service is to provide material related to entrepreneurship development and organizational management, and creativity competitions for OSIS and MPK members between schools. Community service related to entrepreneurship development in the management of Intra-School Student Organizations runs smoothly and in accordance with the desired expectations. Students participate actively in every series of activities held. In addition to participating in the Webinar as the pinnacle of community service, students also participate in the preparation of school creative business proposals, poster making competitions, and Share Content competitions. Thus, community service activities carried out by FISIP Unjani make a positive contribution in providing new understanding and thoughts as well as ideas, ideas, creative innovations that can be applied and implemented in organizations and in the school environment where they study. and form an entrepreneurial spirit, namely a leader who has an entrepreneurial spirit.